Dampak Perubahan Iklim Dapat Meningkatnya Kebakaran Hutan Dan Upaya Pelestarian Lingkungan - Indra Leo Firmansyah; Anita Indah Irma Wati; Indah Permata Sari; Azzahria Maulida Syifa; Denny Oktavina Radianto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Climate change has become a major factor in increasing forest fires in various parts of the world. This phenomenon has had serious impacts on the environment, economy and human health. Environmental conservation efforts are becoming increasingly important to reduce the risk of forest fires and maintain ecosystem balance. With a better understanding of the relationship between climate change and forest fires, preventive and adaptation measures can be designed to protect forests and ecosystems that are vulnerable to this threat. The purpose of this article is to discuss the impact of climate change on the increase in forest fires and environmental conservation efforts that can be taken to overcome this problem. The method used in this research is using a literature study method to collect information about the impact of climate change on forest fires and environmental conservation efforts. Climate change is significantly increasing the risk of forest fires worldwide leading to rising global temperatures that are drying out forests and increasing the likelihood of fires occurring. Changing rainfall patterns also lengthen and strengthen the dry season, increasing the potential for forest fires. These factors, along with human activity and extreme weather, have led to an increase in the frequency and intensity of forest fires. The impacts are far-reaching, including destruction of wildlife habitat, carbon loss, ecosystem degradation, and negative impacts on air quality and human health.